2010
DOI: 10.1161/circep.109.915918
|View full text |Cite
|
Sign up to set email alerts
|

Damage to the Esophagus After Atrial Fibrillation Ablation

Abstract: Background-Radiofrequency catheter ablation is increasingly used in the treatment of atrial fibrillation. Esophageal wall changes varying from erythema to ulcers have been described by endoscopy in up to 47% of patients following pulmonary vein isolation (PVI). Although esophageal changes are frequently reported, the development of a left atrial (LA)-esophageal fistula is fortunately rare. Nevertheless, mucosal changes may just represent "the tip of the iceberg." The aim of this study was, therefore, to invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(33 citation statements)
references
References 33 publications
1
30
0
Order By: Relevance
“…Some of the well-identified UGI system complications, including atrioesophageal fistulae, esophageal ulcerations, gastroesophageal reflux, acute pyloric spasm, and gastric hypomotility, are at least partially a consequence of VN injury. [3][4][5][6][7][8][9][10][11] Because the consequences of UGI injury can be catastrophic, the importance of understanding the effect of AF ablation on VN injury cannot be overstated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some of the well-identified UGI system complications, including atrioesophageal fistulae, esophageal ulcerations, gastroesophageal reflux, acute pyloric spasm, and gastric hypomotility, are at least partially a consequence of VN injury. [3][4][5][6][7][8][9][10][11] Because the consequences of UGI injury can be catastrophic, the importance of understanding the effect of AF ablation on VN injury cannot be overstated.…”
Section: Discussionmentioning
confidence: 99%
“…25,26 It can also be a result of plexi compression from edema resulting from an RFA-induced inflammatory response of the neighboring mediastinal structures (indirect consequence of RFA). 8 Microhematomas from vascular injury during RFA may also cause the same effect on these plexi. 27 It should also be noted that some of UGI dysfunction can be because of direct injury to the intrinsic (myentric) plexi of the esophagus without affecting the VN, through the similar pathological mechanisms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 Due to the high incidence of esophageal injury and potential severity of complications, 1 study suggested follow-up with EGD and endosonography for reevaluation of esophageal injury postablation. 13 However, if AEF is already suspected, it has also been suggested that esophageal procedures be completely avoided due to air embolization as a direct cause from endoscopy. 8 Further safeguards include a reduction Figure 3.…”
Section: Discussionmentioning
confidence: 99%
“…9 In brief, EGD and EUS were performed after receiving written consent from the patient regarding the endoscopic procedure in a fasting state of at least 6 hours before the examination. Sedation was performed by intravenous administration of propofol in a dosage as required for adequate sedation.…”
Section: Egd and Eusmentioning
confidence: 99%